Water Supply Network District Metering Theory and Case Study - Di Nardo, Armando; Di Natale, Michele; Di Mauro, Anna.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The management of a water supply network can be substantially improved defining permanent sectors or districts that enhances simpler water loss detection and pressure management. However, the water network partitioning may compromise water system performance, since some pipes are usually closed to delimit districts in order not to have too many metering stations, to decrease costs and simplify water balance. This may reduce the reliability of the whole system and not guarantee the delivery of water at the different network nodes. In practical applications, the design of districts or sectors is generally based on empirical approaches or on limited field experiences. The book proposes a design support methodology, based on graph theory principles and tested on real case study. The described methodology can help water utilities, professionals and researchers to define the optimal districts or sectors of a water supply network.
Water leakage management -- Water district metering policy and practice -- Design support methodology -- Case study: Monterusciello network -- Conclusion.
Keywords: Engineering; Water-supply.; Civil engineering; Water pollution; Regional economics; Spatial economics; Engineering; Civil Engineering; Water Industry/Water Technologies; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Regional/Spatial Science; Electronic books